Pendidikan dalam Keluarga untuk Mengantisipasi Pengaruh Pemikiran Postmodern bagi Remaja Kristen - Sostenis Nggebu; John Jamlaay; Dony Surachman (Harati: Jurnal Pendidikan Kristen, 2024)
This article presents the problem that teenagers who have not yet been won to Christ are very vulnerable to being influenced by postmodernist thinking. Considering they do not have a solid foundation of faith in Christ. The anticipation is that parents must take the initiative to introduce Jesus to them. The method used in this research is a survey in the form of a questionnaire. The results show that 26 students (65%) out of 40 Christian students at a high school in Bandung City do not yet have a close relationship with Christ. Meanwhile, 14 students (35%) stated that they had experienced new life and had faith in Jesus. This data reflects the attitude of parents who do not fully prioritize spiritual needs in their family. These teenagers are in the midst of a period of panca roba or doubt and are easily influenced by deviant teachings. The challenges faced by spiritual coaches at school are the same as those faced by their parents. The challenge arises to serve and develop them to know Christ personally. In conclusion, winning teenagers to Christ is a priority for parents to anticipate the influence of modernist thinking on them.